Comment on: "Do maternal albumin levels affect post-operative complications after cesarean delivery?" - Shuangqiong Zhou; Xiuhong Cao; Zhiqiang Liu (BMC, 2023)
Abstract Hypoalbuminemia is often considered an independent risk factor for surgical site infections. This study first demonstrated that albumin level ≥ 3.3 g/dL was independently associated with adverse maternal outcomes. In this letter to the editor, we would like to raise some concerns about the study and clarify the interpretation of the results.